Inovasi Pembelajaran Sentra Berbasis Kreatifitas - Muhsinin Muhsinin (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Since the authors doing ofaccompaniment socialization K13 for Teachers ofRaudlatul Atfal in Mojokerto, Jombang and Pasuruan all teacherscomplaints are always the application of learning centers is very expensive.Based on these perceptions, so we do the teaching center in RA SalafiyahSyafiiyahSookoMojokerto. Theresults of accompaniment show that; (1) The Center of Learning Approach is identical with the Innovation and creativity of teachers in preparing the materials, learning media including the making of Educational ofEquipment (APE), and learning management strategy;(2) The capacity of the teachingeducational in a unit of education determines the quantity and quality of the central opening; (3) Creativity of teachers in synergy with Stakes Holders will produce a maximum product innovation; (4) Costly learning center management lies in the expensive of an Idea ornot expensive ideas financially.Keywords: Innovation, Learning Center ( Sentra ), Creatifity